Social stratification through the capabilities approach: the case of the Inuit of Nunavik. - Duhaime, Gérard; Édouard, Roberson (Polar Geography, 2024)
Based on the capabilities approach, this study investigates the Qanuippitaa Survey concerning the health of the Inuit of Nunavik (Canada). The goal was to examine the mutual influences among essential capabilities that affect Inuit adults in their efforts to achieve their aspirations. As shown by our analysis, most essential capabilities (e.g. education, health, employment, income) appear to be limited to certain demographic categories, such as women and older adults; they are at higher risk than others to be exposed to poverty, food insecurity, and violence. However, poor housing conditions and exposure to violence are not discriminant, since they are generalized. The study demonstrates that Nunavik is socially stratified, since all Inuit adults do not enjoy the same capabilities to face contemporary challenges.